2019
DOI: 10.1159/000496356
|View full text |Cite
|
Sign up to set email alerts
|

GPR55-Mediated Effects in Colon Cancer Cell Lines

Abstract: The cannabinoid-responsive G protein-coupled receptor GPR55 and its endogenous ligand L-α-lysophosphatidyl­inositol (LPI) have been reported to play a role in several cancers. A proliferation-enhancing effect of GPR55 has been described for several cancer cell lines and LPI has been found elevated in cancer patients. The aim of this study was to investigate whether GPR55 signaling had an effect on the proliferation of colon cancer cell lines. Using cell viability assays and Western blotting, we show that stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In all cell lines, except MCF-10A and U-87MG, DHA-DA cytotoxicity was at least partially blocked by both of the two GPR55 antagonists used, indicating that GPR55 is a cell line independent target for cell death induction by this compound ( Figure 5 ). These data agree with the literature data on the GPR55 receptor expression in these cell lines [ 4 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In all cell lines, except MCF-10A and U-87MG, DHA-DA cytotoxicity was at least partially blocked by both of the two GPR55 antagonists used, indicating that GPR55 is a cell line independent target for cell death induction by this compound ( Figure 5 ). These data agree with the literature data on the GPR55 receptor expression in these cell lines [ 4 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…As in many other cancer cell lines and tissues, AEA as well as the expression of CB1 was found elevated in CRC [78]. AEA demonstrates an apoptosis-promoting effect per se; this may be interpreted as a selfdefense mechanism.…”
Section: Colorectal Cancermentioning
confidence: 51%
“…GPR55 is part of the endocannabinoid system and its biological function is still under investigation. GPR55 is overexpressed in colon cancerous cells, and may influence ERK1/2 phosphorylation and cell proliferation [ 10 , 11 ]. Carina et al reported that GPR55 is an oncogene in colon cancer, which could contribute to the migration and metastasis of colon cancer cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%